A multi-agency consensus panel examining synergies and differences between evidence-based approaches to violence reduction in England. (November 2021) - Davey, Peter; Forbes, Rachel; Sebire, Jacqueline; Cestaro, David; Firmin, Carlene; Macfarlane, Colin; Bath, Rachel
Abstract: Background: Many approaches to violence reduction are currently being applied across England. As interest in contextual and thematic responses to violence has increased, so have questions about the relationship between approaches that seek to affect the environments in which violence occurs. We sought to outline the collective potential of three of the most common approaches (contextual safeguarding, public health, and problem-solving policing) and produce an instrument to help practitioners to understand how could these approaches be used collectively at a local level. Methods: Colleagues with expertise in, or who were national leads for, public health, contextual safeguarding, and problem-solving approaches formed a professional consensus panel to define the three approaches in practice, the steps required to combine them, and the benefits and challenges of each. The group met virtually for 90–120 min/month between September, 2020, and March, 2021. A panel consensus was reached about how to describe each approach. Ideas were developed and refined independently between meetings through application of approaches to case studies and model development. A practitioner toolkit that set out the findings of the group was co-produced by the professional consensus panel. The practitioner toolkit was distributed to and presented at professional networks. Local authorities were invited to pilot a combined system reform approach, to check how combining the approaches might work in practice. Findings: One of the major findings was that theoretical approaches are often not used as intended by those who created them. The panel showed the similarities and co-dependencies of the approaches and proposed models of using them together in practice. The production of a practitioner toolkit has clarified what the fundamentals of each approach are and provided a space where similarities and differences can be seen. The practitioner resource has received positive feedback and discussions have started in one local authority area to pilot a system approach. Interpretation: To our knowledge, this is the first time a collection of approaches has been brought together to understand their collective benefit in potentially reducing violence. This work provides a foundation for a pilot intervention to assess the effect of combining these approaches on reducing violence. Funding: This project has not received funding from any external organisation or group. The organisations involved have given leave to their members to attend meetings and engage in work related to this group. The South Yorkshire Violence Reduction Unit provided funds to commission a graphic artist to support the presentation of this project.